2008
DOI: 10.1021/bc8002452
|View full text |Cite
|
Sign up to set email alerts
|

Specific Targeting of HER2 Overexpressing Breast Cancer Cells with Doxorubicin-Loaded Trastuzumab-Modified Human Serum Albumin Nanoparticles

Abstract: Specific targeting of tumor cells to achieve higher drug levels in tumor tissue and to overcome cardiotoxic and other secondary effects is the major goal in cancer therapy. With trastuzumab as a humanized monoclonal antibody binding, the HER2 receptor specific targeting is possible. In the present study, target-oriented nanoparticles based on biodegradable human serum albumin (HSA) loaded with cytostatic drug doxorubicin were developed. The surface of the nanoparticles was modified by covalent attachment of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 27 publications
2
78
0
Order By: Relevance
“…9,33,34 Given that HER2, a well known antibody against the HER2/neu receptor overexpressed in breast cancer cells, has been widely used in the clinic for treating patients with HER2 overexpression, developing a potential clinically applicable HER2-targeting nanoparticle imaging probe and drug delivery platform has been an active research area. [35][36][37][38][39][40] Previous investigations have shown the efficiency of bioconjugation of the HER2 antibody to nanoparticles, including iron oxide nanoparticles and 41-43 dumb bell-like Au-Fe 3 O 4 nanoparticles for specific targeting of breast cancer cells and targeted delivery. 44 Our development of HER2-targeted PEO-b-PγMPS copolymercoated IONPs should provide improved HER2 targeting with reduced nonspecific uptake by macrophages and the reticuloendothelial system as well as a prolonged blood circulation time.…”
Section: Specificity Binding and Targeting Of Her2 By Anti-her2-ionpsmentioning
confidence: 99%
“…9,33,34 Given that HER2, a well known antibody against the HER2/neu receptor overexpressed in breast cancer cells, has been widely used in the clinic for treating patients with HER2 overexpression, developing a potential clinically applicable HER2-targeting nanoparticle imaging probe and drug delivery platform has been an active research area. [35][36][37][38][39][40] Previous investigations have shown the efficiency of bioconjugation of the HER2 antibody to nanoparticles, including iron oxide nanoparticles and 41-43 dumb bell-like Au-Fe 3 O 4 nanoparticles for specific targeting of breast cancer cells and targeted delivery. 44 Our development of HER2-targeted PEO-b-PγMPS copolymercoated IONPs should provide improved HER2 targeting with reduced nonspecific uptake by macrophages and the reticuloendothelial system as well as a prolonged blood circulation time.…”
Section: Specificity Binding and Targeting Of Her2 By Anti-her2-ionpsmentioning
confidence: 99%
“…Previous studies have shown promising results for either cancer therapy or imaging via trastuzumab decoration of such nanoparticles as dextran iron oxide nanoparticles, 15 poly(d,l-lactide-co-glycolide)/montmorillonite nanoparticles, 16 poly(dl-lactic acid) nanoparticles, 17 and human serum albumin nanoparticles. [18][19][20] Chitosan is a carbohydrate polymer with the desirable properties of biodegradability and biocompatibility that have made it a candidate polymer for preparation of drug delivery carriers. [21][22][23][24][25][26][27][28][29] Several methods have been developed for the preparation of doxorubicin delivery systems based on chitosan, 30 which include dextran sulfate-chitosan hydrogel nanoparticles, glycol-chitosan nanoaggregates, oleoyl-chitosan nanoparticles, chitosan-poly(acrylic acid) hollow nanospheres, and stearic acid-grafted chitosan oligosaccharide micelles.…”
Section: Introductionmentioning
confidence: 99%
“…1 One example is the conjugation of trastuzumab (Herceptin ® ) to doxorubicin-carrying nanoparticles which allows transport of the chemotherapeutic agent specifically to tumor cells. 2 In addition, antibody-conjugated nanoparticles have the potential to be used in active targeted drug delivery. 3 Other nanoparticles that have been studied for their use in cancer therapies include: iron oxide, 4 poly(D,L-lactide-co-glycolide)/montmorillonite, 5 poly(D,L-lactic acid), 6 nickel, 7 and human serum albumin.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other nanoparticles that have been studied for their use in cancer therapies include: iron oxide, 4 poly(D,L-lactide-co-glycolide)/montmorillonite, 5 poly(D,L-lactic acid), 6 nickel, 7 and human serum albumin. 2,8,9 The development of multidrug resistance (MDR) to anticancer agents by tumor cells is a major obstacle in the chemotherapeutic cure of cancer. 10 Therefore, larger dosages of these anticancer drugs must be applied, leading to increased toxicity; side effects include myelosuppression, carcinogenic effects, alopecia, myalgia, thrombocytopenia, congestive heart failure, and immune suppression.…”
Section: Introductionmentioning
confidence: 99%